DETERMINAN FAKTOR REMAJA MEROKOK STUDI KASUS DI SMPN 27 SEMARANG - Arika Noviana; Emmy Riyanti; Laksmono Widagdo (Jurnal Kesehatan Masyarakat (Undip), 2016)
Indonesia is the third largest cigarette users in the world, over 70% of children exposed to cigarette smoke and bear the risk of various diseases caused by cigarette smoke. The prevalence of coronary heart disease that doctors diagnosed at the age of over 15 years in Indonesia reached 1.5% and the prevalence of COPD has reached 3.7%. According to Riskesdas Central Java in 2013 the number of smokers aged 10-14 years every day at 0.5% and the number of smokers aged 15-19 years every day of 11.2%. In Semarang, start smoking at the age of 10-14 years amounted to 18.0% and amounted to 53.9% of 15-19 years. The purpose of the research to describe and analyze the determinant factors of smoking adolescents in SMPN 27 Semarang. This research is a quantitative and qualitative information extracting with an interview and cross-sectional approach. The instrument used in this study was a questionnaire and an interview guide. The study sample as many as 57 respondents with saturated sampling technique for quantitative and 3 informants triangulation with purposive sampling for qualitative. Analysis of the data used a chi-square test for the bivariate analysis with a significance level of 95%. At 80.7% of respondents have become moderate smokers, while 19.3% of respondents still be light smokers. Bivariate analysis, there was no correlation between age (p = 0.051), parental education respondents (p = 1.000), allowance (p = 0.183), knowledge (p = 0318), conformity adolescents (p = 0.296), affordability of cigarettes (p = 0.742), extracurricular involvement (p = 0.482) and the regulation of smoking in schools (p = 0.462) with the practice of smoking students, and there is a relationship between attitudes (p = 0.03) with the practice of smoking students. Schools can provide information on a regular basis every 1 semester 2 times the discussion on the practice of smoking and the dangers of smoking.